2012
DOI: 10.1371/journal.pone.0034977
|View full text |Cite
|
Sign up to set email alerts
|

The Q705K Polymorphism in NLRP3 Is a Gain-of-Function Alteration Leading to Excessive Interleukin-1β and IL-18 Production

Abstract: BackgroundThe Q705K polymorphism in NLRP3 has been implicated in several chronic inflammatory diseases. In this study we determine the functional role of this commonly occurring polymorphism using an in-vitro system.Principal FindingsNLRP3-WT and NLRP3-Q705K were retrovirally transduced into the human monocytic cell line THP-1, followed by the assessment of IL-1β and IL-18 levels in the cell culture supernatant. THP-1 cells expressing the above NLRP3 variants were sorted based upon Green Fluorescent Protein (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(119 citation statements)
references
References 50 publications
4
113
2
Order By: Relevance
“…The association of the Q705K polymorphism with upregulated CRP levels in unaffected males suggests that the polymorphism may impart an inflammasome-mediated inflammatoty phenotype to males. The polymorphism Q705K in the NLRP3 gene is a gain-of-function polymorphism responsible for the abnormal production of IL-1β leading to the deleterious effect of inflammation (18). During inflammation, IL-1β induced the expression of CRP, suggesting a link between the inflammasome and minor allele of the Q705K polymorphism and CRP present in males (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of the Q705K polymorphism with upregulated CRP levels in unaffected males suggests that the polymorphism may impart an inflammasome-mediated inflammatoty phenotype to males. The polymorphism Q705K in the NLRP3 gene is a gain-of-function polymorphism responsible for the abnormal production of IL-1β leading to the deleterious effect of inflammation (18). During inflammation, IL-1β induced the expression of CRP, suggesting a link between the inflammasome and minor allele of the Q705K polymorphism and CRP present in males (27).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have also revealed the association of the Q705K polymorphism in the NLRP3 gene (rs35829419) with various inflammatory diseases including celiac disease (9), diabetes type-1 (8), abdominal aortic aneurysms (14), Crohn's disease (15) and rheumatoid arthritis (10 CARD8 (C10X) genes was found to be associated with rheumatoid arthritis (10) and Crohn's disease (15,16). Considering a possible key role of the NLRP3 inflammasome in promoting myocardial inflammation (17) and athero sclerosis through the production of pro-inflammatory cytokine IL-1β (18), the aim of the present study was to investigate the effect of Q705K polymorphism in NLRP3 gene and the risk of developing MI in a northern Swedish population.…”
Section: Introductionmentioning
confidence: 99%
“…Several allelic variants of genes encoding danger receptors or molecules associated with signalling pathways from these receptors have been described. [78][79][80] Although complete deficiency of these molecules strongly compromises immune response, these are generally rare events. By contrast, genes for TLRs are highly polymorphic and encode many variants with either higher or lower activity in terms of ligand binding or signal transduction.…”
Section: Future Perspectives On Plasticity and Regulation Of Danger Smentioning
confidence: 99%
“…However, as in many genetic disorders, environmental factors are also effective in the phenotype of the disease, in addition to genetic factors (16)(17)(18)(19)(20). A Swedish study reported increased activity of the CIAS1-Q705K polymorphism as demonstrated by the increased spontaneous and stimulated release of IL-1 beta and IL-18, which are responsible in chronic inflammatory diseases (21). In our study, Q705K polymorphism was detected in 4 patients and 3 individuals in the study and control groups, respectively.…”
Section: Discussionmentioning
confidence: 99%